SOC Estimation of Li-ion Batteries with Learning Rate-Optimized Deep Fully Convolutional Network - Hannan M.A.; How D.N.T.; Hossain Lipu M.S.; Ker P.J.; Dong Z.Y.; Mansur M.; Blaabjerg F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); Convolution; Convolutional neural networks; Deep learning; Ions; Learning systems; Lithium compounds; Lithium-ion batteries; Long short-term memory; Temperature; Battery temperature; Convolutional networks; Learning rates; Lithium ions; Novel architecture; Open sources; SOC estimations; State of charge; Battery management systems